A High Torque Density Dual-Stator Flux-Reversal-Machine with Multiple Poles Halbach Excitation on Outer Stator - Siwei Tang; Yuanying Xu; Chao He; Jiquan Yang (Actuators, 2024)
This paper proposes a high torque density dual-stator flux-reversal-machine with multiple poles Halbach excitation (MPHE-DSFRM), which uses two pole pairs’ numbers (PPNs) of PM excitation on one outer stator tooth, and one PPN of PM excitation on one inner stator tooth. The introduction of different PPNs of PM excitation on the outer and the inner stators can optimize magnetic circuit and airgap flux density. A Halbach array is formed by inserting three pieces of circumferentially magnetized PMs into four pieces of radially magnetized permanent magnets (PMs) on the outer stator, which aims to further enhance torque density, and reduce torque ripple. Based on the flux modulation effect, the analytical modeling of the proposed MPHE-DSFRM is established, together with the evolution process, and the working principle is presented. Then, the key design parameters of MPHE-DSFRM are optimized to achieve high torque density and low torque ripple for high torque quality. Three representative DSFRMs and a conventional FRM are designed and analyzed, and they share the same design key parameters, including PM usage, outer radius of the outer stator, and active airgap length. The electromagnetic performances, including airgap flux density, back electromotive force (back-EMF), and torque characteristics, are analyzed and compared by finite element analysis (FEA). The calculated results show that the proposed MPHE-DSFRM can provide high torque density and high PM utilization.